The Role of Monocyte to High-Density Lipoprotein Cholesterol Ratio in Prediction of Carotid Intima-Media Thickness in Patients With Type 2 Diabetes - Chen, Jia Wei; Li, Chang; Liu, Zhu Hui; Shen, Ying; Ding, Feng Hua; Shu, Xin Yi; Zhang, Rui Yan; Shen, Wei Feng; Lu, Lin; Wang, Xiao Qun (Frontiers in Endocrinology, 2019)
Abstract Background: Chronic inflammatory disorders and dyslipidemia in type 2 diabetes mellitus (T2DM) are essential contributors to the development of atherosclerotic cardiovascular disease. Monocyte to high-density lipoprotein cholesterol (HDL-C) ratio (MHR) is a novel and simple measure associated positively with the body inflammatory and oxidative stress status. However, little is known regarding the role of MHR in evaluating carotid intima-media thickness (CIMT), a surrogate predictor of subsequent vascular events, especially in diabetic patients. Methods: A total of 494 patients with T2DM and 1848 non-diabetic subjects were consecutively enrolled in study 1. Correlation between MHR and CIMT was compared between diabetic and non-diabetic subjects. In study 2, a total of 110 T2DM patients from study 1 with normal basal CIMT and a follow-up ultrasonography at 12 months were enrolled. The predictive role of MHR on CIMT progression in diabetic patients was analyzed. Results: In study 1, MHR was higher in patients with T2DM than non-diabetic subjects (p<0.001). After adjustment for confounding risk factors, MHR remained correlated significantly with CIMT in diabetic (r=0.172, p=0.001) but not non-diabetic (r=0.006, p=0.813) subjects. Logistic regression analyses demonstrated that MHR is superior to traditional lipid parameters in association with elevated CIMT in diabetic patients. In study 2, MHR at baseline was positively correlated with change in CIMT (r=0.313, p=0.001). Basal MHR was independently associated with change in CIMT [β=0.059, (95% CI: 0.012-0.105), p=0.014] in multivariate liner regression analysis. Conclusions: Our study suggest that MHR is a convenient and effective measure in prediction of the presence and progression of subclinical carotid atherosclerosis in patients with T2DM.